2018
DOI: 10.16965/ijar.2017.485
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the Third and Fourth Head of the Biceps Brachii Muscle in Caucasian Race – A Study and Review of Literature

Abstract: Anatomic variations in the heads of biceps brachii are not uncommon. It varies from one head to seven heads but two heads (long and short) are considered normal. In this study, 56 arms from 28 cadavers were studied for third and fourth heads in the anatomy laboratory of Weill Cornell Medicine. We observed supernumerary heads in 5 cadavers (8.92%), out of which three heads were seen in 4 cadavers (7.14%) and four heads in only one cadaver (1.78%). Clinically, these kinds of anomalies are important because super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…The accessory heads express a wide spectrum of possible origins. A total of 69 studies (9054 upper limbs) provided detailed description of the various origin sites (Adachi, 1909; Agarwal & Gopal, 2020; Al‐Kushi, 2013; Asvat et al, 1993; Avadhani & Chakravarthi, 2012; Bagoji et al, 2014; Ballesteros et al, 2014; Bharambe et al, 2015; Chandrupatla & Sultana, 2016; Chauhan, 2010; Cheema & Singla, 2011; Chitra & Kalaiyarasi, 2016; Cucca et al, 2010; da Silva, 2016; da Silva Leal, 1926; Duran & Arquez, 2016; Gheno et al, 2010; Gindha et al, 2015; Greig et al, 1952; Guerrero et al, 2018; Gupta & D'Souza, 2014; Gupta et al, 2020; Ilayperuma et al, 2011; Kervancioglu & Orhan, 2011; Khaledpour, 1985; Kopuz et al, 1999; Kosugi et al, 1992; Kumar et al, 2008; Kumar et al, 2012; Kumar & Baidya, 2018; Le Double, 1897; Lee, 2013; Lingaswamy et al, 2015; Manoj et al, 2012; Mantraratnam & Bhattam, 2016; Morampuri et al, 2015; Mori, 1964; Nalluri et al, 2016; Nasr & Hussein, 2013; Nayak et al, 2006; Neto et al, 1998; Patel et al, 2016; Pathak et al, 2016; Poudel & Bhattarai, 2009; Radhika et al, 2017; Rai et al, 2007; Ravi et al, 2020; Rincon et al, 2002; Rodriguez‐Niedenführ et al, 2003; Ruiz et al, 2017; Salve et al, 2013; Sandeep et al, 2012; Sato, 1969; Sawant et al, 2012; Schwerdtf...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The accessory heads express a wide spectrum of possible origins. A total of 69 studies (9054 upper limbs) provided detailed description of the various origin sites (Adachi, 1909; Agarwal & Gopal, 2020; Al‐Kushi, 2013; Asvat et al, 1993; Avadhani & Chakravarthi, 2012; Bagoji et al, 2014; Ballesteros et al, 2014; Bharambe et al, 2015; Chandrupatla & Sultana, 2016; Chauhan, 2010; Cheema & Singla, 2011; Chitra & Kalaiyarasi, 2016; Cucca et al, 2010; da Silva, 2016; da Silva Leal, 1926; Duran & Arquez, 2016; Gheno et al, 2010; Gindha et al, 2015; Greig et al, 1952; Guerrero et al, 2018; Gupta & D'Souza, 2014; Gupta et al, 2020; Ilayperuma et al, 2011; Kervancioglu & Orhan, 2011; Khaledpour, 1985; Kopuz et al, 1999; Kosugi et al, 1992; Kumar et al, 2008; Kumar et al, 2012; Kumar & Baidya, 2018; Le Double, 1897; Lee, 2013; Lingaswamy et al, 2015; Manoj et al, 2012; Mantraratnam & Bhattam, 2016; Morampuri et al, 2015; Mori, 1964; Nalluri et al, 2016; Nasr & Hussein, 2013; Nayak et al, 2006; Neto et al, 1998; Patel et al, 2016; Pathak et al, 2016; Poudel & Bhattarai, 2009; Radhika et al, 2017; Rai et al, 2007; Ravi et al, 2020; Rincon et al, 2002; Rodriguez‐Niedenführ et al, 2003; Ruiz et al, 2017; Salve et al, 2013; Sandeep et al, 2012; Sato, 1969; Sawant et al, 2012; Schwerdtf...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies (2800 upper limbs) reported the occurrence of the accessory heads of biceps brachii muscle in relation to gender (Al‐Kushi, 2013; Asvat et al, 1993; Ballesteros et al, 2014; Cheema & Singla, 2011; Duran & Arquez, 2016; Gindha et al, 2015; Ilayperuma et al, 2011; Kervancioglu & Orhan, 2011; Koizumi, 1934; Kopuz et al, 1999; Kosugi et al, 1992; Kumar & Baidya, 2018; Le Double, 1897; Lee, 2013; Nasr & Hussein, 2013; Nayak et al, 2006; Rodriguez‐Niedenführ et al, 2003; Ruiz et al, 2017; Salve et al, 2013; Sato, 1969; Sawant et al, 2012; Schwerdtfeger et al, 2018; Shalini & Anupama, 2013; Techataweewan et al, 2016; Verma & Sakthivel, 2019; Wahengbam et al, 2015). Meta‐analysis of the relevant studies revealed that the accessory heads are more prevalent in males (10.2%; 95% CI 7–13%) than in females (7.3%; 95% CI 4–10%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations